Kitāb al-tafṣīl li-jumal al-Taḥṣīl : Sharḥ Kitāb al-taḥṣīl li-muʾallifihi Ḥasan b. Muḥammad al-Raṣṣāṣ - Thiele, Jan,; Ansari, Hassan, (Miras Maktoob, ISBN: 9789004365452., 2019)
From the time of its foundation in 284/897, the Zaydī Imamate of Yemen was home to Muʿtazilī ideas. During the first centuries and starting with Imam al-Hādī ila ʼl-Ḥaqq (d. 298/911), Zaydī ideology included elements very much akin to the opinions of the Baghdad School of the Muʿtazila as founded by Bishr b. al-Muʿtamir (d. 210/825). However, in the 6-7th/11-12th centuries, we see a rise in popularity of Bahshamiyya ideas, a sub-group of the Basran School of the Muʿtazila around Abū Hāshim al-Jubbāʾī (d. 321/933). These ideas were systematized and elaborated upon by the Zaydī theologian al-Raṣṣāṣ (d. 584/1188), notably in his short theological summa the Kitāb al-taḥṣīl fi ʼl-tawḥīd wal-taʿdīl . This work soon gained popularity and within 30 years after his death, as three commentaries on it were written. The one whose surviving part is published here is an early witness of Yemeni Zaydī acquaintance with Ibn al-Malāḥimī's (d. 536/1141) works and anti-Bahshamī teachings.